Self-care practices and associated factors among hypertension patients in public hospitals in Harari regional state and Dire Dawa City administration, Eastern Ethiopia: A multi-center cross-sectional study - Abdisa, Lemesa; Balis, Bikila; Shiferaw, Kasiye; Debella, Adera; Bekele, Habtamu; Girma, Sagni; Mechal, Ayalnesh; Amare, Eldana; Kechine, Temesgen; Tari, Kajela; Nigussie, Kabtamu; Assefa, Nega; et al. (Frontiers in Public Health, 2022)
Introduction Hypertension is a silent killer that causes serious health issues in all parts of the world. Hypertension is a risk factor for cardiovascular disease, stroke, and kidney disease. Self-care practices have been identified as an important component of hypertension management. Despite the government's commitment and the interventions of various stakeholders, the burden of hypertension and its sequel remain unabated. A recent study showed that hypertension self-care practices play a vital role in controlling and managing high blood pressure, even though there is poor self-practice among hypertensive patients in Ethiopia. Therefore, this study assessed the level of self-care practices and associated factors among hypertension patients in public hospitals in Harari regional state and Dire Dawa City Administration, Eastern Ethiopia. Methods Hospital-based cross-sectional study was conducted from June 15 to July 15/2021 among 415 adult hypertensive patients on follow-up. The participants were selected using systematic sampling. Hypertension Self-Care Activity Level Effects (H-SCALE) was used to collect data through face-to-face interviews. The SPSS version 24 was used for analysis. Logistic regression analyses were done to determine the association between the outcome and independent variables. For multivariate logistic regression models, variables having a P < 0.25 during bivariate analysis were candidates. The strength of the association was estimated using AOR and 95% CI. The level of statistical significance was declared at a p < 0.05. Results This study revealed that 52% (95% CI, 48.2–58%) had good level of self-care practices. Formal education (AOR = 3.45, 95% CI: 2.1–4.85), good knowledge about hypertension (AOR = 1.5, 95% CI: 1.17–2.1) 1.5, abstain from chewing khat (AOR = 2.01, 95% CI: 1.44–3.94), strong social support (AOR= 1.9, 95% CI: 1.16–3.1), and absence of depression (AOR = 2.03, 95% CI: 1.43–3.92) were statistically associated with a good level of self-care practices. Conclusions This study pointed out that about half of the participants had a good level of self-care practices. Formal education, good knowledge about hypertension, abstaining from khat chewing, good social support, and absence of depression showed associations with a good level of self-care practices. Therefore, public health interventions on hypertension self-care practices, and strengthening non-communicable diseases control programs are vital. Moreover, the provision of targeted education to patients can improve disease knowledge and self-care practices.